LINGUISTIC ANALYSIS OF DEICTIC CENTER IN AGRICULTURAL TEXTS IN UZBEK AND ENGLISH LANGUAGES - Bozorova Munisa (International Journal of Literature and Language Studies, 2026)
In this paper one the main phenomen of pragmalinguistics the deixis and its role of creating deictic shift in agricultural texts in English and in Uzbek is discussed. The main features of deictic shift using deictic words are shown with the help of the scientific materials taken from scholarly articles and thesis. The pragmatic and cognitive analysis have been provided and the results have been given.